Ideal and Expected Roles of School Guidance Counselors - Rankine, Fred C.; Angus, James T. (Canadian Journal of Counselling and Psychotherapy, 2012)
Ideal role perceptions of New Brunswick counselors were compared with random samples of actual role expectations held for coun- selors by principals, teachers, parents, and students. Scope of the present study included counselors from the major population centers of the province. The significant role disagreements which were obtained in 82 situations are discussed and tentative reasons for such disagreements are offered. A previous study (Rankine & Angus, 1971) which examined the coun- selors' expectations of the other groups compared with the actual role expectations held for counselors by these other groups produced the most role disagreements with students. This study indicates a different pattern, but suggests counselors will be more effective in terms of meeting the students' expectations if they adopt an "ideal" set in relation to conflicts outlined in the Guidance Counselor Role Norm Inventory.